READINESS AND PREPARATION OF LIBRARIANS IN MANAGEMENT AND DEVELOPMENT OF PUBLIC READING PARK (TBM) IN INDONESIA AS AGENT OF SOCIAL CHANGE IN SOCIOLOGICAL PERSPECTIVE - BAKHTIYAR; FAHRIYAH (CV KULTURA DIGITAL MEDIA, 2020)
This study intends to describe the readiness and preparation of librarians in the management and development of TBM as agents of social change in society. Research focuses on an analysis based on a comprehensive detailed study of content that has high and primary urgency, namely the role of TBM as an agent of social change in society. Research has the appropriate scope, precise and unbiased. research is covered in in-depth analysis activities, based on the focus of fundamental and primary studies, on the management of the role of TBM as agents of change in society, through the role of assistance activities utilizing TBM information services.Various analytical activities, it turns out require critical thinking, apply a conceptualization of historical traces in the past or is happening. Therefore, it is very suitable to use historical approach research, which is a research in the form of a critical critical inquiry into the development of a thought. Primary information sources are the most used elements as primary data. In historical approach data collection techniques, utilizing library research is carrying out literacy reading activities that have subject matter, TBM and its role in society, social change agents and TBM information services.Analysis of research uses descriptive qualitative, relying on the source of analysis of various reading material theoretical, research and not research. So that the validity of the research is realized, it requires the empowerment of content analysis, useful for analyzing the meaning of important concepts, the role of TBM and agents of change in society. Observation is used as an important element, to support the construction of the theory. The results showed that; (1) TBM has a strategic role and becomes an agent of social change in society, (2) librarians must have the readiness and thorough preparation of the basic elements for the management and development of TBM as agents of social change.